1988
DOI: 10.1227/00006123-198805000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Posttraumatic Seizures in Children

Abstract: Twenty-two adults with mild concussions were assessed 5 times during the first 3 months after injury. The initial tests were performed within 72 hours of injury. Each evaluation included a neurological examination and neuropsychological reaction time (RT) tests of simple and choice RT variations. The concussed subjects were compared with control subjects matched for age, sex, and education. The time of day of the testing was equated for the two groups. None of the concussed subjects had a significant neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(65 citation statements)
references
References 0 publications
3
58
2
2
Order By: Relevance
“…Most seizures were prolonged or recurrent, but typically responded to treatment with a single AED. Our cohort corroborates the previously established EPTS risk factors of age < 2 years (Ong et al, 1996;Ratan et al, 1999), and severe TBI (Hahn et al, 1988;Marshall et al, 1992;Ong et al, 1996;Ratan et al, 1999), as well the less consistently reported risk factor of NAT (Barlow et al, 2000;Keenan et al, 2003), and SDH (Hahn et al, 1988;Ong et al, 1996). It also identified two other risk factors for EPTS: pre-hospital hypoxia and impact seizures.…”
Section: Independent Risk Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…Most seizures were prolonged or recurrent, but typically responded to treatment with a single AED. Our cohort corroborates the previously established EPTS risk factors of age < 2 years (Ong et al, 1996;Ratan et al, 1999), and severe TBI (Hahn et al, 1988;Marshall et al, 1992;Ong et al, 1996;Ratan et al, 1999), as well the less consistently reported risk factor of NAT (Barlow et al, 2000;Keenan et al, 2003), and SDH (Hahn et al, 1988;Ong et al, 1996). It also identified two other risk factors for EPTS: pre-hospital hypoxia and impact seizures.…”
Section: Independent Risk Factorssupporting
confidence: 91%
“…Accurate identification of children at risk for EPTS can be difficult after moderate or severe TBI (Hahn et al, 1988;Lewis et al, 1993;Ratan et al, 1999). Younger age (Ong et al, 1996;Ratan et al, 1999), and more severe injury (Hahn et al, 1988;Marshall et al, 1992;Ong et al, 1996;Ratan et al, 1999), are the most consistently reported risk factors and are highlighted in the current guidelines for the management of severe TBI in children (Adelson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk increases further in patients with lower Glasgow Coma Scale scores at presentation. [139][140][141][142][143] In a large Danish population study, prior concussion imparted a twofold increased risk of epilepsy in children. 139 Risk was greatest within the first year after concussion, but remained increased for more than 10 years.…”
Section: Posttraumatic Seizures and Epilepsymentioning
confidence: 99%
“…La ISS, que es un sistema de puntuació n Tabla 2 -Escala del coma de Glasgow pediá trica Fuente: Hahn et al11 ; Raimondi et al12 .…”
unclassified